Peran Pemeriksaan Radiologis dalam Identifikasi Awal Kardiomegali untuk Mencegah Penyakit Jantung - Wijaya, Inge Friska; Santoso, Alexander Halim; Wijaya, Bryan Anna; Dinali, Diana; Aziel, Disya Gwyneth (PT. Riset Press International, 2026)
Early detection of cardiomegaly is essential to prevent progression toward heart failure, especially in aging populations where cardiovascular remodeling is common. This community-based program evaluated the use of chest radiography for identifying cardiomegaly while increasing public awareness of cardiovascular risk factors. A total of 99 elderly participants (median age 73 years; 71.7% female) underwent radiographic screening. Cardiothoracic ratio (CTR) assessment showed that 36.4% had cardiomegaly (CTR ≥50%), while 63.6% were within normal limits. Cardiomegaly prevalence was higher in participants over 70 years and more frequent in females. These findings align with known age- and sex-related cardiac remodeling patterns, including postmenopausal estrogen decline, which contributes to hypertension, endothelial dysfunction, and myocardial fibrosis. The program demonstrated that community-based radiological screening is a practical tool for early detection of structural cardiac abnormalities and can support timely referral and preventive care. Despite limitations in design and sample size, the activity highlights the value of integrating simple imaging screening with health education to reduce cardiovascular disease burden.